Analytic Solution of Fractional-Order Heat- and Wave-Like Equations Using Generalized n-dimensional Differential Transform Method - Baranwal, Vipul K.; Pandey, Ram K.; Tripathi, Manoj P.; Singh, Om P. (My University, 2018)
In this paper, we have introduced a generalized n-dimensional differential transform method to propose a user friendly algorithm to obtain the closed form analytic solution for n-dimensional fractional heat- and wave-like equations. Three examples are given to establish the simplicity of the algorithm. In Example 5.3, we show that ten terms of the series representing the solution, even in fractional order, give a very accurate solution. © 2011 Verlag der Zeitschrift für Naturforschung, Tübingen.
Keywords: Generalized n-Dimensional Differential Transform Method; n-Dimensional Fractional Heat- and Wave-Like Equation; Caputo Fractional Derivative